Perancangan dan Pembuatan Sistem Informasi Perpustakaan pada Maple Leaf Centre - Anggono, Hendry Nugroho; Santoso, Leo Willyanto; Setiabudi, Djoni Haryadi (Jurnal Infra, 2013)
Maple Leaf Centre library still use manual way to borrow and return books. Maple Leaf Centre library has a software-based desktop application, but it is not used because it does not fit the needs of the library. In searching catalog system, user get difficulty to get information about library collection. In addition to the need to catalog search system, it is necessary also means proper circulation to facilitate the circulation of books and improve the quality of the library. In this final project, Iâm developed the website of Library Information Systems.The design is developed by using Power Designer 15. Interface website is created by Macromedia Dreamweaver 8. The software is created by Hypertext Preprocessor (PHP) and MySql for database server. Library Information System Applications for Maple Leaf Centre has been implemented include the manufacture admin and generate reports. That feature have been made include procurement module, collections processing, circulation (lending transaction, return transaction, extension transaction, reservation transaction and fines payment transactions), member area, and FAQ.